2011
DOI: 10.1002/j.2050-0416.2011.tb00488.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Protein Digestibility Sorghums on Free Amino Nitrogen (FAN) Production during Malting and Mashing

Abstract: In sorghum brewing, obtaining sufficient Free Amino Nitrogen (FAN) for rapid and complete fermentation remains a problem due to the high proportions of unmalted sorghum used and the poor digestibility of wet-heat treated sorghum protein. Sorghum mutant lines with high protein digestibility have been developed through breeding. These high protein digestibility sorghums (HPDS) have protein bodies with villi-like borders that apparently facilitate protease access. This work investigated FAN production from HPDS w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…The large increase in fermentable sugars is undoubtedly due to the combined activity of the malt amylase enzymes and the exogenous amylases. Similarly, the very large increase in FAN was due to the combination of malt and exogenous protease enzymes .…”
Section: Resultsmentioning
confidence: 93%
“…The large increase in fermentable sugars is undoubtedly due to the combined activity of the malt amylase enzymes and the exogenous amylases. Similarly, the very large increase in FAN was due to the combination of malt and exogenous protease enzymes .…”
Section: Resultsmentioning
confidence: 93%
“…For example, sorghum lines with high protein digestibility have been developed where synthesis of certain kafirin sub‐classes, including specifically γ ‐kafirin, have been inhibited by chemical mutation or genetic modification . Research has shown that FAN in sorghum malt and FAN and extract in raw sorghum grain brewing can be substantially improved with the use of such sorghums.…”
Section: Future Directionsmentioning
confidence: 99%
“…Nitric–perchloric acid digestion of the raw flour and spent grain samples was performed as described . The iron, zinc, magnesium, calcium and phosphorus contents of the digested flour, digested spent grain and wort were measured by inductively coupled plasma optical emission spectrometry (ICP‐OES; Optima 5300 DV, PerkinElmer, Johannesburg, South Africa).…”
Section: Methodsmentioning
confidence: 99%